2021
DOI: 10.33963/kp.a2021.0031
|View full text |Cite
|
Sign up to set email alerts
|

Right coronary artery patency as a modulator for unprotected left main PCI risk: myth or reality?

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Finally, some studies showed that in stable patients undergoing unprotected left main PCI, CTO of the right coronary artery (RCA) may be associated with increased risk of periprocedural complications and mortality [27,28]. This may be because during unprotected left main PCI, a large region of myocardium is jeopardized, and in the absence of a patent RCA, hemodynamic deterioration is more likely [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, some studies showed that in stable patients undergoing unprotected left main PCI, CTO of the right coronary artery (RCA) may be associated with increased risk of periprocedural complications and mortality [27,28]. This may be because during unprotected left main PCI, a large region of myocardium is jeopardized, and in the absence of a patent RCA, hemodynamic deterioration is more likely [28].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some studies showed that in stable patients undergoing unprotected left main PCI, CTO of the right coronary artery (RCA) may be associated with increased risk of periprocedural complications and mortality [27,28]. This may be because during unprotected left main PCI, a large region of myocardium is jeopardized, and in the absence of a patent RCA, hemodynamic deterioration is more likely [28]. However, not all studies found a negative effect of the lack of RCA flow on outcomes, which may be partially explained by differences between studies in left main PCI complexity, clinical characteristics of included patients, or clinical context [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation